Problem Based Learning Model Based On Image Media In Mastering Mufradat And Kalam For Arabic Language And Literature Students/ نموذج التعلم المبني على المشكلة القائم على الوسائط الصورية في إتقان مفردات ومهارة الكلام لطلبة القسم اللغة العربية وآدابها - Mawardy, Naja Alwi (Ijaz Arabi Journal of Arabic Learning, 2024)
This research aims to explain the problem-based learning model in the Department of Arabic Language and Literature, Sayyid Ali Rahmatullah State Islamic University, Tulungagung, Indonesia. The research method used is a qualitative approach, especially phenomenology. Data collection techniques include observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and conclusion. Apart from that, literature data analysis uses descriptive analysis and content analysis. This research will focus on discussions related to the role of lecturers as planners, implementers, and evaluators in the application of problem-based learning models based on image media in mastering vocabulary and speaking skills. The research results show that the problem-based learning model used in "kalam" learning is based on visual media and is oriented toward solving problems related to the images presented. The results of this research are the planning stage, which is achieved through discussions between assigned lecturers via invitation in the WhatsApp group, followed by the implementation steps. Stage I involves student orientation on specific problems. In Phase II, students are organized to learn. Stage III sees the lecturer guiding the investigation. Stage IV involves students developing and presenting their work. Finally, in Stage V, the problem-solving process is analyzed and evaluated. The evaluation process occurs when students carry out group discussions and play roles. The assessment includes linguistic and non-linguistic aspects. For this reason, the role of lecturers is essential in mastering vocabulary and speaking skills using Arabic for students.